Reading "Cultural Village": Actor Collaboration and Cultural Capital in Wonosari, Gunungkidul - Amboro, Joko; Wahyuningsih, Novita (Mimbar Agama Budaya, 2025)
This study investigates the transformation process of Wonosari Village, Gunungkidul Regency, towards achieving its status as a Cultural Village (Desa Budaya). The research employs a descriptive qualitative approach with data collection methods encompassing participant observation and in-depth interviews with 15 key informants. The central research focus is to answer: How do the roles of actors and the forms of cultural capital drive cultural preservation and the creative economy in Wonosari?. The findings indicate that Wonosari Village has more than 45 active cultural groups, reflecting a rich array of traditional arts, customs, and local culinary heritage. Culture is understood as social and economic capital that can spur creative economic growth and strengthen local identity. Cultural preservation in this region involves multi-stakeholder synergy, ranging from the village government, the DIY Regional Culture Office, art communities, and formal educational institutions, which function as facilitators, curators, and agents of cultural value transmission. However, cultural preservation faces four primary obstacles: modernization, insufficient regulation, limited funding, and weak documentation. Preservation strategies are directed towards strengthening cultural institutions, community participation, leveraging village funds (dana desa), and digital-based documentation. This study emphasizes the importance of collaborative and community-based approaches in positioning culture as the main axis of inclusive, sustainable, and competitive village development.